THE EFFECT OF LEADERSHIP AND WORK ABILITY ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING - Ritonga, Husni Thamrin; Syaifuddin; Faris, Salman; Nasution, Myrna Pratiwi (Social Economics, 2024)
The research objective of this article is to examine the factors that influence and how to utilize resources to be managed in accordance with company goals. Human resources are one of the most important factors in the organization, because the quality of the organization itself is highly dependent on the quality of human resources as employees and service actors in an organization. Therefore, to get human resources in accordance with the needs of a strategy in managing human resources, good human resource management will provide progress for the company, especially in dealing with situations and conditions that are always changing and developing. Organizations also have goals that need to be carried out by leaders who provide impetus, cause, channel, and maintain the behavior of employees so that they are willing to work in accordance with what the organization wants. The theoretical and practical aspects of functional tasks relate to how well employees get the job done, while behavioural tasks relate to the ability of employees to handle inter-personal activities with other members in the organization including overcoming conflict, managing time, empowering others, working in a group and working independently. The relationship between leadership and work ability on employee performance can be improved through the use of authority to direct subordinates in doing work to achieve the goals of the organization, carrying out the tasks assigned to them based on skills, experience, and sincerity and time. This research was conducted at the Labuhan Batu Regency Regional Revenue Agency which has the status of Civil Servants totalling 57 people. The inductive analysis map according to Ni Kadek Yuli developed and presented in the identification shows that Work Ability, Work Facilities and Motivation on Employee Performance have a positive and significant effect on employee performance. The direction of the influence of this variable is also positive, which means that the higher the ability of an employee to complete his duties and responsibilities and good facilities, it motivates employees to improve their performance. The scientific and practical tools of the process approach in managing work leadership and capabilities have been automated. The article states that good leadership is basically a leader who is able to make decisions, motivate, communicate, and control subordinates. Meanwhile, work ability is a result of work achieved or a person’s expertise in carrying out the tasks assigned to him based on skills, experience, and seriousness and time.